Oral biofilm composition and phenotype in caries-active and caries-free children - Boisen, Gabriella; Brogårdh-Roth, Susanne; Neilands, Jessica; Mira, Alex; Carda-Diéguez, Miguel; Davies, Julia R. (Frontiers in Oral Health, 2024)
IntroductionDuring development of dental caries, oral biofilms undergo changes in microbial composition and phenotypical traits. The aim of this study was to compare the acid tolerance (AT) of plaque from two groups of children: one with severe caries (CA) and one with no caries experience (CF) and to correlate this to the microbial composition and metabolic profile of the biofilms.MethodsDental plaque samples from 20 children (2–5 years) in each group were studied. The AT was analyzed by viability assessment after exposure to an acid challenge (pH 3.5), using LIVE/DEAD® BacLight™ stain and confocal microscopy. Levels of acid tolerance (AT) were evaluated using a scoring system ranging from 1 (no/low AT), to 5 (high/all AT). Metabolic profiles were investigated following a 20 mM glucose pulse for one hour through Nuclear Magnetic Resonance (NMR). Microbial composition was characterized by 16S rRNA Illumina sequencing.ResultsThe mean AT score of the CA group (4.1) was significantly higher than that of the CF group (2.6, p < 0.05). When comparing the end-products of glucose metabolism detected after a glucose-pulse, the CA samples showed a significantly higher lactate to acetate, lactate to formate, lactate to succinate and lactate to ethanol ratio than the CF samples (p < 0.05). The bacterial characterization of the samples revealed 25 species significantly more abundant in the CA samples, including species of Streptococcus, Prevotella, Leptotrichia and Veillonella (p < 0.05).DiscussionOur results show that AT in pooled plaque from the oral cavity of children with severe caries is increased compared to that in healthy subjects and that this can be related to differences in the metabolic activity and microbial composition of the biofilms. Thus, the overall phenotype of dental plaque appears to be a promising indicator of the caries status of individuals. However, longitudinal studies investigating how the AT changes over time in relation to caries development are needed before plaque AT could be considered as a prediction method for the development of dental caries.